DAMPAK KONFLIK RUSIA-UKRAINA TERHADAP PERJANJIAN PERSAHABATAN ANTAR RUSIA DAN UKRAINA - Julian Daniel; Arlina Permanasari (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2022)
International relations or international relations are human interactions between nations eitherindividually, or in groups that are carried out directly or indirectly. The existence of a number ofmajor countries in this world is a reality that cannot be denied anymore. The inequality of naturalresources and industries that encourage countries to work together gives rise to a norm so thateach country is not only concerned with its interests, but all actions or relations made with othercountries must pay attention to the rules of international law that arise both based oninternational treaties, international customs, general legal principles and judgments of scholars,international organizations or international institutions so as to achieve a legal order that doesnot interfere with peace, international security and justice.